Abundance of Lutzomyia longipalpis (Diptera: Psychodidae: Phlebotominae) and urban transmission of visceral leishmaniasis in Campo Grande, state of Mato Grosso do Sul, Brazil - Alessandra Gutierrez de Oliveira; Eunice Aparecida Bianchi Galati; Orcy de Oliveira; Gilliard Rezende de Oliveira; Italo Alexander Cabello Espindola; Maria Elizabeth Cavalheiros Dorval; Reginaldo Peçanha Brazil (Memorias do Instituto Oswaldo Cruz, 2006)
The outspread and urbanization of visceral leishmaniasis (VL) in Campo Grande, state of Mato Grosso do Sul, lead us to undertake the present study over diversity and abundance of sand flies in the urban area to compare with previous search carried out during 1999/2000, before the identification of the disease in the human population.The captures were carried out with automatic light traps, weekly, from February 2004 to February 2005 on three sites including a forested area (Zé Pereira), two peridomicilies (shelters of domestic animals and cultivation areas), and intradomicilie. In the present study 110 collections were obtained during 13 months for 1320 h of collections, resulting in 5004 specimens, 3649 males and 1355 females belonging to the 20 following species: Brumptomyia avellari, Brumptomyia sp., Bichromomyia flaviscutellata, Evandromyia lenti, E. termitophila, E. cortelezzii, E. borrouli, Lutzomyia sp., L. longipalpis, Micropygomyia quinquefer, N. antunesi, N. whitmani, Pintomyia christenseni, Pi. damascenoi, Psathyromyia aragaoi, Ps. campograndensis, Ps. hermanlenti, Ps. shannoni, Pychodopygus claustrei, and Sciopemyia sordellii. L. longipalpis was the most abundant species in the anthropic environment with 92.22% of the captures. This shows an increase of sixty times in the density of L. longipalpis compared to the last sand fly evaluation in 1999/2000. The high density of L. longipalpis in Campo Grande is the main factor of risk in transmission of the disease to human in the urban area. The capture of N. antunesi, typical specie from Amazonian region, in Mato Grosso do Sul is reported for the first time.